2022
DOI: 10.1111/tbed.14735
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid substitution in the VP2 protein of Indian foot‐and‐mouth disease virus serotype O vaccine strain confers thermostability and protective immunity in cattle

Abstract: Foot‐and‐mouth disease (FMD) is a significant threat to animal health globally. Prophylactic vaccination using inactivated FMD virus (FMDV) antigen is being practised for the control in endemic countries. A major limitation of the current vaccine is its susceptibility to high environmental temperature causing loss of immunogenicity, thus necessitating the cold chain for maintenance of its efficacy. Hence, the FMD vaccine with thermostable virus particles will be highly useful in sustaining the integrity of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…It is reported that capsid thermostability could be improved by mutations of amino acids in the region of VP2 and VP3 proteins (Mateo et al 2003(Mateo et al , 2008. Based on our earlier study of immune response in cattle (Biswal et al 2022), the specific amino acid change in The growth kinetics study of recombinant viruses revealed the attainment of maximum titer by 12-18 hpi by all viruses. However, the growth of Y2098FΔ3A virus was delayed initially with lesser titer, but all the recombinant viruses attained similar titer by 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that capsid thermostability could be improved by mutations of amino acids in the region of VP2 and VP3 proteins (Mateo et al 2003(Mateo et al , 2008. Based on our earlier study of immune response in cattle (Biswal et al 2022), the specific amino acid change in The growth kinetics study of recombinant viruses revealed the attainment of maximum titer by 12-18 hpi by all viruses. However, the growth of Y2098FΔ3A virus was delayed initially with lesser titer, but all the recombinant viruses attained similar titer by 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant plasmid was designated as pT7-OR2/75. The viral VP2 region constituting thermostable mutation Y2098F was amplified from thermostable virus (Biswal et al 2022) using the L482F and EcoRI-R3 primers. The amplicon was digested with Nhe I (New England Biolabs, USA, #R0131S) and Bsu36 I (New England Biolabs, USA, #R0524S) and used to replace the corresponding fragment in pT7-OR2/75.…”
Section: Generation Of Recombinant Cdna Clonementioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid chain of VP4 forms a three-turn helix, and the myristoylated C-terminus is close to the three-fold axis, while the N-terminus is near the five-fold axis of the particle [ 61 ]. Five copies of the VP1 subunit are positioned along the five-fold symmetry, while three copies of each VP2 and VP3 subunit alternated within the three-fold axis of the capsid, and the VP4 subunit is located internally [ 77 ]. Studies have identified negligible adaptive substitutions in VP4, which were identified but not functionally characterized, which limits the comprehensive understanding of their effects on the virus.…”
Section: Adaptive Amino Acid Substitutions In Capsid Proteinsmentioning
confidence: 99%
“…Stabilizing additives such as disaccharides [17][18][19], amino acids [20], detergent [21], metal ions [19,22], etc. have been reported for various viruses, including FMDV, and research on stabilizing FMDVs by amino acid substitution of viral capsid proteins is being conducted worldwide [23][24][25]. Among these, divalent transition metal ions have been found to contribute to the stabilization of FMDV particles by forming salt bridges at the inter-pentameric interface of the FMDV capsid [26], which is known to vary depending on factors such as the virus strain [27].…”
Section: Introductionmentioning
confidence: 99%